FORMULASI NANOKRIM EKSTRAK DAUN KATUK (Sauropus androgynus L.Merr.) SEBAGAI PELEMBAB KULIT - Chandra, Devina; Rohana Sinaga, Taruli; Rudi Aman Manik, Tumpak; Kristiani Aruan, Tina (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2021)
Katuk (Sauropus androgynus (L.) Merr.) leaves have benefits for the human body to protect cell structure and work up vitamin C activity. Cream is a semi-solid preparation which contain one or more dissolved medicinal ingredients in a suitable base material and containing not less than 60% water. Nanocream has an easy, comfortable diffusion on the skin area and increases the absorption of active substances on the skin. This research aims to formulate 3% katuk leaf extract as a skin moisturizer in the form of nanocream preparations with a comparison using blanks (without extract) and Citra brand products. This research was conducted by using an experimental method. The research steps are plant identification, simplicity characterization, screening test, the sample was extracted by maceration for 5 × 24 hours using 80% ethanol solvent then the filtrate was evaporated by a vacuum rotary evaporator at approximately 500C for ±5 hours until a thick extract of katuk leaves was produced. The thick extracts of katuk leaves and blanks (without extract) were formulated in Nanocream preparation by using a high-shear emulsification method (high-shear stirring) using a mixer for 8 hours. Then the organoleptic test, homogeneity test, emulsion test, pH test, viscosity test, irritation test by using 6 volunteers with an age range of 20-30 years and humidity test by using 9 volunteers using a skin analyzer from before use to after use for 4 week. The results of the katuk leaf extract nanocream and blank nanocream (without extract) obtained were homogeneous, remained stable, the emulsion type was o/w, the irritation test did not cause skin irritation and the results of the moisture test were the preparation without extract (blank) from 21.3% to 40.1%, the preparation of katuk leaf extract 3% from 21.3% to 40.8% , and stock image products from 22.6% to 38.9%. The results of the analysis showed that the use of katuk leaf extract nanocream gave changes to dry skin conditions for the better and faster increase in water content in the skin so as to obtain a moisturizing effect on the skin.